Investigation of regional total electron content (TEC) values at different ionospheric layers / Ahmad Nizam Abdullah - Abdullah, Ahmad Nizam (2009)
The ionosphere plays a vital role in radio communication and have own characteristics depend on their region. This is dependent on the solar and geomagnetic activity of the earth. The purpose of this project is to investigate TEC parameter at different regional such as northern, equatorial and southern region based on different ionospheric layers. The measurements of TEC were extracted from GPS data supplied by Department of Survey and Mapping Malaysia (JUPEM), Australian Regional GPS Network and Northern California Earthquake Data Center which in RINEX format. The regional of TEC were analyzed in different time. The factors that influence the value of TEC are depending to the altitude, time and region (latitude). The TEC is proportional with altitude and inverse proportional with latitude. So that, it is vital to have different ionospheric propagate at different region. At November, the incoming solar radiation is more directly to Northern hemisphere surface and less at Southern hemisphere . So that the ionization process at northern region is more than the ionization at Southern region. The analysis TEC is important to monitor behavior of the ionosphere as well as for practical application like satellite tracking, satellite to satellite communication, satellite to ground communication and all communication system by using satellite like satellite TV and satellite telecommunication. GPS signals can be used to extract ionospheric parameters such as TEC. Several factors affect the quality of real-time ionospheric delay estimation, such as multipath, GPS satellite and receiver L1/L2 differential delays, cycle slips, etc. Dual frequency carrier-phase and code-delay GPS observations are combined to obtain ionospheric observable related to the slant TEC along the satellite receiver line of sight. This results in the absolute differential delay and the remaining noise is discarded. The TEC itself is hard to accurately determine from the slant TEC because this depends on the sunspot activity, seasonal, diurnal and spatial variations and the line of sight which includes knowledge of the elevation and azimuth of the satellite etc